Factors Related To Schizoprenia Patients’ Ability In Performing Self-Treatment - Desak Made Ari Dwi Jayanti; Dewa Putu Arwidiana (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: Schizophrenia is one of mental disorder occurring and raising number of problems. One of which is the ability in performing self-treatment. This phenomenon suggests that there be declination of motivation in performing self-treatment. Methods: The research purposed to know the factors related to schizophrenia patient’s ability in performing self-treatment. This research used descriptive correlation with cross-sectional approach. The samples taking were done by random sampling with 155 persons with schizophrenia as samples. The bivariate examination used Spearmen test. Results: The result of the research suggested that p value = 0,771; 0,959; 0,473; 0,500; 0,818; 0,837; 0,956 for each variable; sex, age, hallucination, delusion, violence behavior risk, the length of treatment, and the length of getting mental disorder with ability in performing self-treatment. It indicates that there is not any relationship between one variable with another. Meanwhile, variable in social isolation disturbance in body image and frequency related to how many times getting treatment with the ability in performing self-treatment. Each variable was found that p value were at 0,001; 0,001; 0,002 (p value <0, 0005). Conclusion: Those values indicate that there is relation between one variable to another. Further nursing intervention is needed to improve the ability of schizophrenia patients to perform self-care